Pengaruh Perputaran Modal Kerja, Perputaran Persediaan, Perputaran Kas Dan Perputaran Piutang Terhadap Profitabilitas Pada Perusahaan Basic Industry And Chemicals Di Bursa Efek Indonesia Periode 2017-2021 - Ekel Hagana Sinuhaji; Theo Batara Tarigan; Agnes Anjeli; Ike Rukmana Sari; Dio Agung Herubawa (Journal of Economic, Bussines and Accounting (COSTING), 2023)
The epurpose eof ethis estudy ewas eto eexamine ethe eeffect eof eWorking eCapital Turnover, Inventory eTurnover, eCasheTurnover eand eAccounts eReceivable Turnover eon eProfitability in eBasic eIndustry eand eChemical eCompanies eonethe Indonesia eStock eExchange efor ethe 2017-2019 eperiod. eThe eapproach eused ein this estudy eis eaeQuantitativeApproach. eThe type eof eresearch eused eis edescriptive research, ebecause ethis eresearch eis ebased eonethe quantity eand eanalysis eof edata obtained efrom estatistical edata eprocessing. eThe edata processing emethodeused ein this estudy eis eMultiple eLinear eRegression. There are 88 population of Basic Industry and Chemicalscompanies listed on the Indonesia Stock Exchange for the 2017-2021 period, the number of samples used in this study were 17 companies engaged in the Basic Industry and Chemicals sector which were listed on the Indonesia Stock Exchange. The results of this study found that working capital turnover has a positive but not significant effect onprofitability. Inventory Turnover has a positive and significant effect on Profitability. Cash Turnover has a negative and significant effect on profitability. Accounts Receivable Turnover has a positive and significant effect on Profitability. The results of the study can be concluded that the coefficient of determination (R^2) was found to be 0.805, which means that all variables in this study together are able to influence profitability by 80.5%, the remaining 19.5% is explained by other variables or factors. Keywords: Accounts Receivable Turnover; Cash TurnOver; Inventory Turnover; Profitability; Working Capital Turnover